Mental health literacy and help-seeking among unemployed people with mental health problems. (3rd May 2020) - Waldmann, Tamara; Staiger, Tobias; Oexle, Nathalie; Rüsch, Nicolas
Abstract: Background: Unemployed people with mental health problems often do not use available mental health services. Help-seeking may depend on knowledge, recognition and attitudes associated with mental health – a concept referred to as mental health literacy (MHL). Aim: To investigate the influence of MHL on help-seeking intentions and behaviors among unemployed individuals with mental health problems. Methods: A total of 301 unemployed individuals with mental health problems were recruited mainly from employment agencies in Southern Germany. MHL was assessed by the Mental Health Knowledge Schedule (MAKS), the Depression Literacy Scale (DLS), and the Depression with Suicidal Thoughts Vignette. Help-seeking intentions and behaviors were measured using the General Help-Seeking Questionnaire (GHSQ). Associations between MHL and help-seeking intentions and behaviors were tested using regression analyses and structural equation modeling (SEM). Results: All three MHL scales were significantly positively associated with help-seeking intentions and behaviors. In our SEM model, greater MHL was significantly associated with increased intentions and behaviors to seek help from health professionals (formal help) and from family and friends (informal help). Conclusions: Among unemployed persons with mental health problems, programs to improve MHL could facilitate formal as well as informal help-seeking. Future research should examine the efficacy of MHL-interventions to increase help-seeking.